DESKRIPSI FONETIS VOKAL DAN DIFTONG BAHASA KERINCI DI DESA SIMPANG TIGA RAWANG KECAMATAN HAMPARAN RAWANG KOTA SUNGAI PENUH - Tessa Tri Tersya; Amril Amir (EDU RESEARCH, 2024)
This study aims to describe the Vowel Phonetics and Diphthongs of Kerinci Language in Simpang Tiga Rawang Village, Hamparan Rawang District, Sungai Penuh City using a qualitative descriptive approach. The data is in the form of Kerinci Language data in Simpang Tiga Rawang Village based on the Sever Pop vocabulary list. The location of the study was at SD Negeri 032/XI Simpang Tiga Rawang. The presence of the researcher as an observer. The research instrument was the researcher himself. To obtain data, the researcher chose several people as informants. The data sources came from students of SD Negeri 032/XI Simpang Tiga Rawang and the speech of native speakers of Kerinci Language in Simpang Tiga Rawang Village. The data collection method is a careful method using the capture technique and a listening method using the recording technique. The data validity testing technique is triangulation assisted by 2 students of SD Negeri 032/XI Simpang Tiga Rawang and 1 trigulator who is not an informant to check the accuracy of the collected data. The results of the study showed that there are 6 vowels, namely [a][i][u][e][o][ǝ], 13 diphthongs, namely [eu], [ei], [ea], [oi], [ui], [ua], [ue], [iu], [au], [ai], [ae], and [әi], and [әu]. From the results of the study, it can be concluded that the Kerinci language in Simpang Tiga Rawang Village, Hamparan Rawang District, Sungai Penuh City uses more diphthongs than vowels in everyday language.